2021
DOI: 10.1063/5.0037513
|View full text |Cite|
|
Sign up to set email alerts
|

The relaxation dynamics of single flow-stretched polymers in semidilute to concentrated solutions

Abstract: Recent experiments on the return to equilibrium of solutions of entangled polymers stretched by extensional flows [Zhou and Schroeder, Phys. Rev. Lett. 120, 267801 (2018)] have highlighted the possible role of the tube model's two-step mechanism in the process of chain relaxation. In this paper, motivated by these findings, we use a generalized Langevin equation (GLE) to study the time evolution, under linear mixed flow, of the linear dimensions of a single finitely extensible Rouse polymer in a solution of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…Expressions for the X n ( t ) variables themselves are found from eqs – by applying Laplace transforms to the equations, solving the resulting algebraic equations by matrix inversion, and then Laplace inverting the result. In this way, if one defines the Laplace transform of a function f ( t ) by the relation , it can be shown that where and a ̂ n ( s ) = s ζ + b λ n +k , with denoting the inverse Laplace transform operation.…”
Section: Theorysupporting
confidence: 65%
See 4 more Smart Citations
“…Expressions for the X n ( t ) variables themselves are found from eqs – by applying Laplace transforms to the equations, solving the resulting algebraic equations by matrix inversion, and then Laplace inverting the result. In this way, if one defines the Laplace transform of a function f ( t ) by the relation , it can be shown that where and a ̂ n ( s ) = s ζ + b λ n +k , with denoting the inverse Laplace transform operation.…”
Section: Theorysupporting
confidence: 65%
“…Within this approximation, it is readily shown that Here, τ̅ is a dimensionless time defined as τ̅ = τ/τ 1 , with τ 1 given by τ 1 = ζ N 2 l 2 /(3π 2 k B T ). In the special limit α = 1 corresponding to elongational flow, eq reduces to while in the limit α = 0 corresponding to shear flow, it reduces to Furthermore, in the limit κ → 0, both eqs and recover results derived earlier for the case of non-self-interacting chains. , …”
Section: Chain Relaxationmentioning
confidence: 99%
See 3 more Smart Citations